POTENSI PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI DUSUN WAEL SERAM BAGIAN BARAT - Palinussa, Elizabeth; Pattinasarany, Maureen M; Tuhumury, Semuel F; Rijloy, Stefanno M. A. (Universitas Mataram, 2024)
Aquaculture in Indonesia has become a community endeavor because it can help increase sources of income. Seaweed is one of the biota that can be cultivated which is often known as seaweed and then used as a business for coastal communities. The potential for the development of aquaculture areas in Wael Hamlet can be seen with community activities almost entirely as seaweed farmers. The success of seaweed farming is determined by the right cultivation methods, good environmental quality, and management of activities to increase productivity. The purpose of community service is to know the process of seaweed cultivation activities to develop the potential of coastal community cultivation in Wael Hamlet. The activity took place in August 2023 in Wael Hamlet, West Seram Regency. This activity was carried out using the question and answer method of the Community Service team from the Aquaculture Study Program to the seaweed cultivation group in Wael Hamlet. With the stages of activity preparation and activity implementation. The result of the activity is that the activity of utilizing the potential of fishery resources in Wael Hamlet is more towards cultivation and focuses on seaweed cultivation with the type of seaweed developed, namely eucheuma cottonii. The cultivation method used in Wael Hamlet is long line. The cultivation business has been carried out since 2004 and until now. Government assistance has been provided to aquaculture business groups. Where the length of seaweed rearing can reach 45 days. Almost 99% of the people in Wael hamlet are seaweed farmers, showing that this business is very helpful for the community. The conclusion of the community service activities is that the business of seaweed cultivation activities starts from the selection of seeds to the production process.